The Asymmetry of the Mandible in Patients with Unilateral Temporomandibular Joint Disc Displacement Confirmed by Magnetic Resonance Imaging - Tomislav Badel; Stevo Vojnović; Dino Buković; Dijana Zadravec; Sandra Anić Milošević; Mia Smoljan Basuga; Matea Prenc; Ivana Savić Pavičin (Acta Stomatologica Croatica, 2023)
Objectives: The study aimed to determine the relationship between the mandibular asymmetry index according to Kjellberg between patients with painful unilateral anterior disc displacement (DD) and asymptomatic volunteers without disc displacement. Vertical measurements were performed on a panoramic single-image radiograph, and the disc status was confirmed by magnetic resonance imaging (MRI). Material and methods: Two groups of subjects were retrospectively selected, 40 patients (the overall mean age was 35.5 years; 75% female) with temporomandibular disorder symptoms confirmed by RDC/TMD axis I and manual functional analysis. Unilateral DD was determined by MRI. A comparative group of asymptomatic volunteers (20 dental students with a mean age of 23.4 years; 72% female) had the physiological position of the disc determined by MRI. The vertical asymmetry of the condyle was determined by the method of Kjellberg et al. The symmetry of the gonial angle of the mandible was also measured. Results: A comparison of the mean of the asymmetry index between patients (average 90.89±7.08%) and asymptomatic volunteers (mean 95.86±4.44%) showed a statistically significant difference (p=0.0029). There was no difference (p=0.088) in gonial angle symmetry between the patients (mean 96.48±2.96°) and the asymptomatic volunteers (mean 97.52±2.31°). The distribution of the presence of individual DD diagnoses (partial and total displacement with reduction, displacement without reduction) in patients diagnosed with asymmetry of the mandible was without statistical significance (p>0.05). Conclusion: This study actually points to the asymmetry of the mandible as a potential morphological risk of anterior DD.